Reformasi Peradilan Pidana Indonesia Dengan Integrasi Penilaian Risiko Residivisme Untuk Pemidanaan Adil - Reza Seby Alfikri; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This research aims to explore the integration of recidivism risk assessment in Indonesia's punishment system with a more objective and data-based approach. The method used is normative research with a comparative legal approach, which compares the implementation of recidivism risk assessment systems in other countries with the practice in Indonesia. The results show that although recidivism risk assessment has the potential to improve justice and criminal justice effectiveness, there are major challenges in the form of inconsistency in the definition of recidivism, lack of clear time standards, and unfairness in rehabilitation assessment. Therefore, deep legal reforms and the use of data-driven methods balanced with humanitarian aspects are needed to create a more transparent and fair system. Suggestions from this research include the importance of developing clear standards regarding recidivism and increasing the capacity of judicial officers through training. In addition, the development of an objective data-based recidivism risk assessment system and strengthening collaboration between the public and private sectors in social reintegration are needed to achieve a more effective and fair criminal justice system.